2009
DOI: 10.1007/s11419-009-0070-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous analysis of mitragynine, 7-hydroxymitragynine, and other alkaloids in the psychotropic plant “kratom” (Mitragyna speciosa) by LC-ESI-MS

Abstract: speciosa abuse is a matter of major concern. The present analytical method is considered useful for the screening of M. speciosa products in the drug market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 19 publications
8
85
3
Order By: Relevance
“…We found multiple commercial Kratom products to have concentrations of 7-hydroxymitragynine that are substantially higher than those found in raw M. speciosa leaves [16,27,30]. Our findings strongly suggest adulteration of commercial Kratom products with 7-hydroxymitragynine, a plant alkaloid with potent mu-opioid receptor activity, a practice that increases the abuse liability and addictive potential of Kratom products.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We found multiple commercial Kratom products to have concentrations of 7-hydroxymitragynine that are substantially higher than those found in raw M. speciosa leaves [16,27,30]. Our findings strongly suggest adulteration of commercial Kratom products with 7-hydroxymitragynine, a plant alkaloid with potent mu-opioid receptor activity, a practice that increases the abuse liability and addictive potential of Kratom products.…”
Section: Discussionmentioning
confidence: 59%
“…Our findings strongly suggest adulteration of commercial Kratom products with 7-hydroxymitragynine, a plant alkaloid with potent mu-opioid receptor activity, a practice that increases the abuse liability and addictive potential of Kratom products. For example, concentrations of mitragynine and 7-hydroxymitragynine in raw M. speciosa leaves range between 23.6-24.0 μg/mg and 114-134 ng/mg, respectively [30]. Comparison of naturally occurring 7-hydroxymitragynine concentrations with the Phoria products listed in Table 2 demonstrates striking deviation from what would be expected.…”
Section: Discussionmentioning
confidence: 91%
“…The LODs and LOQs ranged from 0.26 to 1.1 and from 0.78 to 36 pg/ml, respectively. In addition, Kikura-Hanajiri et al reported on simultaneous analysis of mitragynine, 7-hydroxymitragynine and other indole alkaloids (speciogynine, speciociliatine, and paynantheine) in the psychotropic plant "kratom" (M. speciosa) [177].…”
Section: Alkaloidsmentioning
confidence: 99%
“…Lower doses tend to yield a dopaminergic-dominant result or stimulation, while higher doses result in a mu-opioid receptor-dominant effect, which eclipses the dopaminergic expression or physical and emotional hedonia and pain relief [12,24,35,36]. Many analytical approaches have been reported for the separation and identification of kratom, including GC and GC-MS [2,3,[37][38][39], LC and LC-MS [38,[40][41][42][43][44] and CE and CE-MS [43,45,46]. In this study, we report a rapid and effective method for quantification mitragynine and 7-hydroxymitragynine compounds in human urine matrix.…”
Section: Introductionmentioning
confidence: 99%